PHRASEOLOGICAL UNITS WITH COLOR COMPONENTS AND THEIR IMPORTANCE IN ENGLISH LANGUAGE - Rajabaliyeva, Nodiraxon (QO‘QON UNIVERSITETI XABARNOMASI, 2024)
Phraseological units, often referred to as idiomatic expressions or set phrases, are combinations of words whose meanings are not derived from the individual meanings of their components. In English, many phraseological units incorporate color terms, enriching the language with cultural, emotional, and metaphorical depth. This article explores the role of color-related phraseological units in English, analyzing their origins, cultural significance, and psychological impact. We will also examine how these expressions contribute to the richness of the English language, reflecting societal attitudes, emotional states, and historical contexts. This article offers analysis of phraseological units containing color elements in the English language, uncovering the underlying values, emotions, and cultural attitudes embedded in these expressions. By exploring a range of colors—red, blue, green, white, and black—within idioms, proverbs, and fixed expressions, the study demonstrates how colors move beyond their literal and aesthetic meanings to carry complex evaluative and connotative significance. The research adopts a multimodal approach, integrating qualitative analysis of cultural, historical, and emotional contexts with quantitative analysis of the distribution and frequency of color-based PUs across different types of texts. The findings emphasize the importance of color in English phraseology as a medium for conveying a wide range of human experiences, emotions, and cultural narratives. This axiological framework not only enriches our understanding of the emotive and connotative power of language but also highlights the influential role of cultural values in shaping linguistic expressions. The study makes a valuable contribution to the field of linguistic axiology by providing insights into how language reflects and constructs societal values and attitudes through the lens of color.